Alpine Snow Algae Microbiome Diversity in the Coast Range of British Columbia - Yakimovich, Kurt M.; Engstrom, Casey B.; Quarmby, Lynne M. (Frontiers in Microbiology, 2020)
Snow algae blooms contain bacteria, fungi, and other microscopic organisms. We surveyed 55 alpine snow algae blooms, collecting a total of 68 samples, from 12 mountains in the Coast Range of British Columbia, Canada. We used microscopy and rDNA metabarcoding to document biodiversity and query species and taxonomic associations. Across all samples, we found 173 algal, 2739 bacterial, 380 fungal, and 540 protist/animalia OTUs. In a previous study, we reported that most algal species were distributed along an elevational gradient. In the current study, we were surprised to find no corresponding distribution in any other taxa. We also tested the hypothesis that certain bacterial and fungal taxa co-occur with specific algal taxa. However, despite previous evidence that particular genera co-occur, we found no significant correlations between taxa across our 68 samples. Notably, seven bacterial, one fungal and two Cercozoan OTUs were widely distributed across our study region. Taken together, these data suggest that the expected mutualisms with algae may not be taxon specific. We also report evidence of snow algae predation by rotifers, tardigrades, springtails, chytrid fungi, and ciliates, establishing the framework for a complex food web.